PENGEMBANGAN GAME PEMBELAJARAN INTERAKTIF MATEMATIKA BANGUN RUANG SISWA KELAS 6 SD - ahmad zainudin; Agus priyadi; Andik Prakasa Hadi; ALDO KRISDIANANTA (UNIVERSITAS STEKOM, 2024)
Mathematics is one of the important subjects. Mathematics is also a subject that is difficult to understand. Understanding concepts is the most important part of learning mathematics, meaning that in studying mathematics students must first understand mathematical concepts in order to be able to solve problems and be able to apply this learning in the real world. Based on direct observations and interviews with grade 6 teachers at SD Negeri 02 Getas, teachers have difficulties in the theme of lesson 3 about